2021
DOI: 10.1017/s0142716421000333
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in language competence of 4-year-old children: Female advantages are mediated by phonological short-term memory

Abstract: For some time now, psycholinguistic research has involved the study of sex differences in language development. Overall, girls seem to have an early advantage over boys, mainly in regard to vocabulary, which appears to decrease and, eventually, vanish with age. While there are numerous studies on sex differences in the acquisition of vocabulary as well as grammar, early sex differences in phonological short-term memory (PSTM) have been mostly neglected, or if research was conducted, it resulted in null finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 95 publications
0
2
0
2
Order By: Relevance
“…The same is valid for the correlations between NWRT results and questionnaire items on the quality and quantity of the language input (see Table 1). Indeed, numerous intra- and extralinguistic variables, such as length and phonological complexity of test items (Cilibrasi et al, 2018), children’s biological sex (Lange & Zaretsky, 2021), and familial socioeconomic status (Korecky-Kröll et al, 2019), just to name a few, contribute to the performance on NWRT. Obviously, bilingualism is only one of many factors influencing the results of working memory tests.…”
Section: Discussionmentioning
confidence: 99%
“…The same is valid for the correlations between NWRT results and questionnaire items on the quality and quantity of the language input (see Table 1). Indeed, numerous intra- and extralinguistic variables, such as length and phonological complexity of test items (Cilibrasi et al, 2018), children’s biological sex (Lange & Zaretsky, 2021), and familial socioeconomic status (Korecky-Kröll et al, 2019), just to name a few, contribute to the performance on NWRT. Obviously, bilingualism is only one of many factors influencing the results of working memory tests.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it would be more inclusive to reveal studies examining gender differences in language on both the content and the linguistic level. Current literature does not generally encompass both; some studies focused on gender differences only on the linguistic level (Lange & Zaretsky, 2021), and some other studies demonstrated gender differences only in emotional content (Svane et al, 2022). To reach a more precise and more generalizable conclusion about gender differences in language, either linguistic variables or content variables such as emotional expression, all studies should be summarized, and a conclusion should be drawn based on the findings.…”
Section: Background Of the Studymentioning
confidence: 99%
“…En relación con las diferencias en el rendimiento lector según el género de los estudiantes, los hallazgos sugieren que estas diferencias comienzan desde edades tempranas (Lange & Zaretsky, 2021) y que las niñas alcanzan mayores puntajes que los niños (O' Dea et al, 2018). Sin embargo, la evidencia no es convergente, ya que algunos estudios señalan que tales desigualdades en el rendimiento no existen (Gallego Ortega et al, 2019).…”
Section: Introductionunclassified
“…Sin embargo, la evidencia no es convergente, ya que algunos estudios señalan que tales desigualdades en el rendimiento no existen (Gallego Ortega et al, 2019). Gran parte de las investigaciones se ha centrado en el vocabulario y en estudiantes desde segundo año básico, pero en menor medida existen hallazgos que apunten a las brechas de género en la adquisición de habilidades lectoras tempranas, como la conciencia fonológica (Lange & Zaretsky, 2021) y la conciencia de lo impreso, así como también es escasa la evidencia relacionada con estudiantes preescolares.…”
Section: Introductionunclassified